The Role of Digital Marketing Social Media Tiktok, Instagram, Twitter on Purchasing Decisions on Gacoan Noodles - Tsabitah, Sahlaa; Perdana, Muhammad Aditya; Erna Apriani; Indra Permana; Abdul Latif (Sumber Belajar Sejahtera, 2025)
TikTok, Instagram, and Twitter have great potential in increasing brand awareness and user engagement, especially among the younger generation. Research shows that interactive and engaging content on TikTok and Instagram tends to be more effective in attracting attention than platforms like Facebook. This study aims to evaluate the influence of using TikTok, Instagram, and Twitter on consumer purchasing decisions for Gacoan Noodle products. While social media is now an important tool in digital marketing, its effectiveness in directly influencing consumer purchasing decisions still needs to be fully understood. This study used a quantitative approach with a Partial Least Square (PLS) model to measure the relationship between variables. The sample consisted of social media users exposed to Mie Gacoan content across the three platforms, with data obtained through an online survey. The validity and reliability analysis results revealed that only the TikTok, Instagram, and Twitter variables met the criteria with an AVE value of more than 0.50. In contrast, the purchase decision variable did not meet these conditions. The results showed that the influence of the three social media platforms on purchasing decisions for Gacoan Noodles was not significant. TikTok has a coefficient of 0.236 with a p-value of 0.299, Instagram 0.166 with a p-value of 0.342, and Twitter 0.217 with a p-value of 0.361. All p-values are more significant than the significance threshold of 0.05. Thus, this study concludes that the three platforms are more effective in raising brand awareness than driving direct purchase decisions.